Global corporate bond issuance: what role for US quantitative easing? - Marco Lo Duca; Giulio Nicoletti; Ariadna Vidal Martinez (European Central Bank (ECB), 2014)
The paper investigates the impact of US quantitative easing (QE) on global non-financial corporate bond issuance. It distinguishes between two QE instruments, MBS/GSE debt and Treasury bonds, and disentangles between two channels of transmission of QE to global bond markets, namely flow effects (purchases) and stock effects (holdings). We control for a number of domestic and global macro-financial factors. In particular, we control for weaknesses in crossborder and domestic banking which might have induced the corporate sector to issue more bonds. The results indicate that US QE had a large impact on corporate bond issuance, especially in emerging markets, and that flow effects (i.e. portfolio rebalancing) were the main transmission channel of QE. A counterfactual analysis shows that bond issuance in emerging markets since 2009 would have been halved without QE.
Keywords: E52; E58; F42; G15; 330; bond issuance; crisis management; emerging markets; Federal Reserve; monetary policy; Quantitative Easing; spill-overs; United States